PENGELOLAAN GERAKAN LITERASI SEKOLAH DALAM MENDUKUNG KEMAMPUAN KARYA TULIS SISWA SEKOLAH DASAR DI SD NEGERI 1 LELONG - Munawir Gazali; Made Ayu Pransisca (LPPM Institut Pendidikan Nusantara Global, 2021)
Reading and writing are part of many learning routines that cannot be separated from everyone's life. UNESCO has released data on reading interest in the world and shows Indonesia's demand for reading is at 0.001. This means that for every 1,000 residents, there is only 1 person who has an interest in reading (Universitas Gadja Mada, 2017). The objectives of this study are 1) to describe the management, planning, implementation, and evaluation of the School Literacy Movement (GLS): 2) to describe the supporting and inhibiting factors for the solution; 3) Describe the results in overcoming the factors that hinder the solution in the management of the School Literacy Movement (GLS) to support writing at SD Negeri 1 Lelong. This research uses descriptive qualitative, which means the type of research is literal data with factors in the field. Data collection techniques used in this study were interviews, observation, and documentation analysis. Researchers used data analysis in the field with the Miles and Huberman model. The steps in the data analysis process carried out by the author are 1) Data collection; 2) Data Reduction; 3) Data Presentation; and 4) Verification. The results of the study, in the management of the School Literacy Movement (GLS) to support student writing at SD Negeri 1 Lelong there are three stages, as follows: planning, implementation and evaluation